Determinants of Handwashing Practices in Kenya : The Role of Media Exposure, Poverty and Infrastructure - Schmidt, W. P.; Aunger, R.; Coombes, Y.; Maina, P. M.; Matiko, C. N.; Biran, A.; Curtis, V. (2012)
BACKGROUND To explore how structural constraints such as lack of reliable water supply, sanitation, educational and other socio-economic factors limit the adoption of better hygiene. METHODS In preparation for the Kenya National Handwashing Campaign, we conducted a nationwide cross sectional survey in 800 households with two components: (i) direct structured observation of hygiene practices at key junctures (food handling, cleaning a child after defaecation, toilet use), followed by (ii) a structured interview addressing potential socio-economic, water access and behavioural determinants of handwashing. RESULTS We observed a total of 5182 critical opportunities for handwashing, and handwashing with soap at 25% of these. Handwashing with soap was more often practised after faecal contact (32%) than in connection with food handling (15%). In univariate and multivariate analysis, water access, level of education, media exposure and media ownership were associated with handwashing with soap. Only households with very poor access to water and sanitation, and with the lowest levels of education and media exposure, washed their hands markedly less than the majority of the households. CONCLUSION The results underscore that structural constraints can limit hygiene practices in the very disadvantaged sections of a population, thus jeopardizing the potential success of hygiene promotion campaigns in those most at risk of disease. Nevertheless, the strong association of handwashing with media ownership and exposure supports the view that mass media can play a role in hygiene promotion.